Twenty First Meeting of the National Development Council Summary Record New Delhi October 27 and 28, 1964 - Planning Commission (Planning Commission, 1964)
Welcoming participants to the twenty first meeting of the National Development Council, the PRIME MINISTER said that this was the first meeting of this Council which would not have the guidance of Shri Jawaharlal Nehru, the late Prime Minister. It was his vision that led to the introduction of planning in India and it was his example and advice that inspired many other developing countries. As long ago as in 1938, soon after popular Governments were formed in the Provinces, a National Planning Committee was set up under Shri Jawaharlal Nehru’s Chairmanship and it was again he who decided, as the first Prime Minister of India, to set up the Planning Commission in 1950 and to constitute the National Development Council. He was no longer with us but the objectives which he had set before the country were there to guide us. This was indeed a heavy burden and the Prime Minister sought the cooperation of the Council in order that he may be able to discharge his responsibilities adequately and he suggested that the Council should meet at more frequent intervals say every two or three months until final shape had been given to the Fourth Five Year Plan.
Government of India Planning Commission